The effects of eccentric phase duration on concentric phase force production during depth jumps - Dorgo, S.; Smith, D. R.; Ortiz, M.; King, G. A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of the study was to test the yet unproven theory, which states that the faster a muscle is stretched the greater force it produces in the subsequent concentric phase during plyometric exercises. Thirty-three trained male athletes performed plyometric depth jumps from two heights (trial A=33.02cm, trial B=47.94cm) landing on a force platform, followed by an immediate counter jump. Researchers determined the duration of eccentric phase and the relative peak concentric force of each jump using the data from the force platform. Results indicated a significant inverse relationship between eccentric duration and relative peak concentric force in both trials (p=0.019 and p<0.001). This relationship was stronger as the height of the depth jump increased (r=-0.40 in trial A and r=-0.62 in trial B).